PENGARUH PENDEKATAN DEEP LEARNING BERBASIS CONCEPT MAPPING TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA DI SD NEGERI 023 KEBUNSARI - Andini, Putri; Faisal, Muhammad; Rahman, Hardianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research uses a quantitative approach with a type of experimental research in the form of Quasi Experimental Design. The problem addressed in this study was the low level of students’ critical thinking skills at SD Negeri 023 Kebunsari. Based on it, the formulation of research problem are: (1) how is the implementation of the deep learning approach based on concept mapping among students at SD Negeri 023 Kebunsari? (2) how are the critical thinking skills of students at SD Negeri 023 Kebunsari? (3) is there any effect of the implementation of the deep learning approach based on concept mapping on students’ critical thinking skills at SD Negeri 023 Kebunsari? The independent variable in this study was the deep learning approach based on concept mapping, while the dependent variable was students’ critical thinking skills. The research population of this study consisted of all students of SD Negeri 023 Kebunsari total of 45 students, while the research samples were grade V.A students with 23 students as the experimental calss and grade V.B with 22 students as the control class. The Data collection techniques used in this research were observation of learning implementation, performance test which was conducted twice critical thinking skills test in the form of multiple-choice questions administered through pretest and posttest, as well as documentation. Data were analyzed using descriptive and inferential statistics with the Mann-Whitney test. The results showed that students’ critical thinking skills in the experimental class increase after being given the concept mapping treatment. Based on hypothesis testing, the significance value was less than 0.05, indicating that there is an effect of the implementation of the deep learning approach based on concept mapping on students’ critical thinking skills at SD Negeri 023 Kebunsari.